Phenomenology for therapists : researching the lived world - Finlay, Linda, 1957- (Hoboken, N.J. : J. Wiley, 2011)
This book provides an accessible comprehensive exploration of phenomenological theory and research methods and is geared specifically to the needs of therapists and other health care professionals. An accessible exploration of an increasingly popular qualitative research methodologyExplains phenomenological concepts and how they are applied to different stages of the research process and to topics relevant to therapy practiceProvides practical examples throughout.
Front Matter -- The Phenomenological Project: Concepts, Theory and Philosophy. Part Introduction -- Phenomenology: Bridging the Practiceb6(BResearch Divide? -- The Phenomenological Project -- The Body in Lived Experience -- Philosophical Foundations -- The b1(BPhenomenological Attitudeb2 (B-- Phenomenological Research Approaches. Part Introduction -- Descriptive Empirical Phenomenology -- Hermeneutic Phenomenology -- Lifeworld Approaches -- Interpretative Phenomenological Analysis -- First-Person Approaches -- Reflexive-Relational Approaches -- Phenomenological Methods in Practice. Part Introduction -- Planning the Research -- PhenomenologicalMethods in Practice. Gathering Data -- Relational Ethics -- The Process of Analysing Data -- Producing the Research -- Evaluating Research -- Appendix -- References -- Index.s
Includes bibliographical references and index.
Print version record.
Keywords: Psychotherapy -- Methodology; Phenomenology; Spiritual care (Medical care); Psychotherapists; Allied Health Personnel; Electronic books; Electronic books